2004
DOI: 10.1128/jb.186.17.5883-5898.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella enterica Subspecies I Genovars by Use of Microarrays

Abstract: Subspecies 1 of Salmonella enterica is responsible for almost all Salmonella infections of warm-blooded animals. Within subspecies 1 there are over 2,300 known serovars that differ in their prevalence and the diseases that they cause in different hosts. Only a few of these serovars are responsible for most Salmonella infections in humans and domestic animals. The gene contents of 79 strains from the most prevalent serovars were profiled by microarray analysis. Strains within the same serovar often differed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
181
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(203 citation statements)
references
References 31 publications
20
181
0
1
Order By: Relevance
“…Small genetic differences between closely related bacteria can lead to considerable phenotypic diversity. For example, the species Salmonella enterica comprises six subspecies, only one of which is pathogenic to mammals (64). Furthermore, expression of phenotypic traits of a given species varies with ecological contexts, such as the single-strain vs. whole-community context, culture media vs. amphibian host, or laboratory vs. field.…”
Section: Coordinated Laboratory and Field Studies Show Bd Infection Dmentioning
confidence: 99%
“…Small genetic differences between closely related bacteria can lead to considerable phenotypic diversity. For example, the species Salmonella enterica comprises six subspecies, only one of which is pathogenic to mammals (64). Furthermore, expression of phenotypic traits of a given species varies with ecological contexts, such as the single-strain vs. whole-community context, culture media vs. amphibian host, or laboratory vs. field.…”
Section: Coordinated Laboratory and Field Studies Show Bd Infection Dmentioning
confidence: 99%
“…The authors are applying such technology to S. Typhimurium in calves, pigs and chickens with the aim of assigning roles to most transposable genes in intestinal colonization. It is vital that such data are integrated with data on the content of S. enterica subspecies I genomes as evaluated by genome-sequencing and microarray analysis (Porwollik et al 2004;Anjum et al 2005), data on gene expression from transcriptome and proteome studies, and data on metabolism and regulatory networks, since this may lead to testable predictions about the basis of host-specificity. Analysis of complete genome sequences has indicated that broad host range serovars (e.g.…”
Section: Molecular Basis Of Intestinal Colonization Of Food-producingmentioning
confidence: 99%
“…Limited intraserovar diversity was established although the serovars tested had extensive geographic and source differences [87]. The DNA array has been a powerful approach for genomic comparisons of many important pathogens [15,22,24,44,81]. A high level of gene gain or loss was revealed in all the lineages of S. enterica and S .…”
Section: Typingmentioning
confidence: 99%